2021
DOI: 10.1038/s41598-021-85325-z
|View full text |Cite
|
Sign up to set email alerts
|

An intercomparison of the pore network to the Navier–Stokes modeling approach applied for saturated conductivity estimation from X-ray CT images

Abstract: Different modeling techniques can be used to estimate the saturated conductivity of a porous medium based on computed tomography (CT) images. In this research, two methods are intercompared: direct modeling using the Navier–Stokes (NS) approach and simplified geometry pore network (PN) modeling. Both modeling approaches rely on pore media geometry which was determined using an X-ray CT scans with voxel size 2 μm. An estimate of the saturated conductivity using both methods was calculated for 20 samples prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Sufian et al [41] showed that the PNMs accurately predict the drops in pressure between pores when compared to numerical solutions of the Navier-Stokes equations. Gackiewicz et al [15] also showed that PNMs computed with the maximum-ball and Delaunay method agreed with FEM solutions to the Navier-Stokes equations for sphere packed materials. PNM computation falls mainly into four categories: Delaunay tesselation of grain centers, maximum-inscribed ball transform of the void space, medial-axis transform, and watershed-based segmentation.…”
Section: Related Workmentioning
confidence: 73%
“…Sufian et al [41] showed that the PNMs accurately predict the drops in pressure between pores when compared to numerical solutions of the Navier-Stokes equations. Gackiewicz et al [15] also showed that PNMs computed with the maximum-ball and Delaunay method agreed with FEM solutions to the Navier-Stokes equations for sphere packed materials. PNM computation falls mainly into four categories: Delaunay tesselation of grain centers, maximum-inscribed ball transform of the void space, medial-axis transform, and watershed-based segmentation.…”
Section: Related Workmentioning
confidence: 73%
“…Thus, we converted the void structure into a pore network for quantitative analysis based on graph theory by regarding the pores and their interconnections as a network. 31,32 According to the watershed algorithm, the pores were segmented from the void structure via gradual thresholding based on the distance map of the void voxels and had the average volume of 1.65 × 10 4 nm 3 (Figures 4E and 6B). 33−35 The obtained network was arranged by assigning repulsive force to the pores and adding gravity between the connected pores (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…This highly connected porous structure of the mesoporous silica particle led to differences in the regional properties with changes in the connectivity of each fraction. Thus, we converted the void structure into a pore network for quantitative analysis based on graph theory by regarding the pores and their interconnections as a network. , According to the watershed algorithm, the pores were segmented from the void structure via gradual thresholding based on the distance map of the void voxels and had the average volume of 1.65 × 10 4 nm 3 (Figures E and B). …”
Section: Resultsmentioning
confidence: 99%
“…The microdimensional design of the geometry was the subject of our study, with due consideration given to its porosity. Consequently, there is no necessity to incorporate the porosity term into the equations as it has been accounted for within the geometry. , …”
Section: Methodsmentioning
confidence: 99%